BAKSO BERBASIS JAMUR TIRAM PUTIH DAN IKAN PATIN PADA KONDISI KEMASAN VAKUM, NON VAKUM SERTA SUHU DINGIN DAN SUHU BEKU SELAMA PENYIMPANAN - Febri ' Muliady; Faizah ' Hamzah; Yusmarini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to discover the effect of packaging and storage temperature conditions on the storability of white oyster mushroom meatballs and catfish that meet the quality standards of fish balls (SNI 01-2346-2006). This study was experimentally conducted using a completely randomized design (CRD). Results of analysis of variance showed that the condition of packaging and storage has significant effects on the moisture content and the microbial population during storage on weeks 0, 1, 2, 3, 4, has no significant effect on thiobarbituric acid and storage acidity in weeks 0, 1, 2 but has real effect on storage in weeks 3 and 4, has no significant effect on descriptive sensory evaluations of storage attribute in weeks 0 and 1 but has real effects on the storage in weeks 2, 3 and 4, has no significant effects on the storage aroma attributes in weeks 0, 1, 2 and 3 but has significant effect on the storage in week 4. White oyster mushroom meatballs and catfish are consumable until storage in the first week. This is because the total microbial population has exceeded the maximum limit set by fish balls Indonesian National Standards (SNI) in the the next week’s storage. Condition of vacuum packaging and freezing temperatures stroge treatment was chosen in this study with water content of 74.34 to 74.36%, thiobarbituric acid from 1.09 to 1.13 mg/kg malonaldehyde, the total microbial population 8.8×9.3×106-106, acidity of 6.46 to 6.45, with no slimy appearance and with white oyster mushroom and catfish aroma. Keyword : Meatballs, white oyster mushroom, catfish, cold and freezing temperature storage, vacuum and non-vacuum packaging